Cutaneous sporotricosis - Akhtar, N; Begum, M; Saleh, AA; Paul, HK; Uddin, MJ; Chowdhury, AQ (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):458-61 The abstract of this article is available on the PubMed website